PENERAPAN METODE SFA (STOCHASTIC FRONTIER ANALYSIS) DALAM PEMBERDAYAAN MASYARAKAT DI DESA MOOTINELO, KWANDANG, GORONTALO UTARA - Wila Rumina Nento; Arafik Lamadi; Moh. Muchlis Djibran (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract North Gorontalo Regency has great potential in the fisheries sector, the sea area reaches 587.6 km2 with a coastline length of 79.6 km (13.5% of the coastline of Gorontalo Province). One of the potential priorities in the aquaculture sector is vaname shrimp. One of the vaname shrimp cultivation centers in North Gorontalo Regency is Mootinelo Village which is located in Kwandang District. Shrimp ponds in Mootinelo Village are still classified as conventional with traditional management methods. Apart from the inadequate level of knowledge of the farmers, environmental quality that is less supportive, disease attacks and non-standard feeding are also factors causing the production of white shrimp in Mootinelo Village to not be optimal, which of course has an impact on the income of the farmers which is still classified as moderate or even low. . With an effort to approach technical efficiency, namely through the SFA (Stochastic Frontier Analysis) method, the main problems faced by partners, namely aspects of basic knowledge regarding the technical aspects of vaname shrimp cultivation and product processing aspects, can be resolved. In this case, there has been an increase in the knowledge of the 'Vaname Jaya' cultivator group regarding the technical characteristics and efficiency of cultivation using the SFA method, as well as an increase in skills in making processed shrimp products, namely eby furai. Abstrak Kabupaten Gorontalo Utara memiliki potensi yang besar di bidang perikanan, luas perairan laut mencapai 587,6 km2 dengan panjang garis pantai 79,6 km (13,5% dari panjang pantai Provinsi Gorontalo). Salah satu potensi yang menjadi prioritas di bidang akuakultur adalah udang vaname. Salah satu sentra budidaya udang vaname di Kabupaten Gorontalo Utara adalah Desa Mootinelo yang terletak di Kecamatan Kwandang. Tambak udang di Desa Mootinelo masih tergolong konvensional dengan metode pengelolaan yang tradisional. Selain tingkat pengetahuan para petambak yang belum memadai, kualitas lingkungan yang kurang mendukung, serangan penyakit, serta pemberian pakan yang tidak standar juga merupakan faktor penyebab produksi udang vaname di Desa Mootinelo tidak maksimal, yang tentunya berimbas pada pendapatan para petambak yang masih tergolong sedang bahkan rendah. Dengan adanya suatu upaya pendekatan efisiensi teknis yaitu melalui metode SFA (Stochastic Frontier Analysis), dimana permasalahan utama yang dihadapi mitra yaitu aspek pengetahuan dasar mengenai teknis budidaya udang vaname dan aspek pengolahan produk dapat teratasi. Dalam hal ini, terjadi peningkatan pengetahuan kelompok pembudidaya ‘Vaname Jaya’ mengenai karakteristik dan efisiensi teknis budidaya melalui metode SFA, serta peningkatan keterampilan dalam membuat produk olahan udang yakni eby furai.